Efforts Of Islamic Religious Education Teachers In Improving The Quality Of Learning In Elementary Schools - Baiq Siti Hajar; Faridl Musyadad; Munarti Munizu; Lukman Affandi; Gamar Al Haddar (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
The purpose of this study was to find out and analyze Islamic religious education instructors who have improved the quality of education in elementary schools. The research method is qualitative with the type of literature review research. Primary data sources consist of; educational and scientific literature books as well as books that are closely related to research using qualitative research methods involving literature studies. The results of research on Islamic religious education conducted at SDIT Multazam do not place cognitive aspects as the only goal, because Islamic knowledge must ultimately be applied in everyday life. The emphasis is on affective and psychomotor aspects, such as students' ability to practice Islamic religious teachings in everyday life, such as Duha prayers, memorizing the Koran, and congregational midday prayers.